Analisis faktor-faktor penyerapan tenaga kerja di Karesidenan Pekalongan tahun 2017-2022 - Putriy, Riska Meylinda; Nurhayati, Siti Fatimah (Journal of Economics Research and Policy Studies, 2024)
Pekalongan Residency faces significant economic challenges, especially in terms of low labor absorption. Economic growth, unemployment rate, minimum wage and investment are some of the factors that have the potential to influence it greatly. This study aims to estimate the effect of GRDP, district minimum wage, unemployment, and investment on labor absorption in the Pekalongan Residency in 2017–2022. The analysis technique used is panel data regression. The Chow and Hausman test analysis shows an optimal fixed effect model. The test results show that unemployment and district minimum wage affected labor absorption in the Pekalongan Residency in 2017-2022. Gross regional domestic product and investment did not affect labor absorption in the Pekalongan Residency in 2017-2022.